An investigation into the precipitation of Fe(III) oxyhydroxides in lime neutralization processes - Mangunda, Cledwyn Tawanda (Department of Chemical Engineering, 2020)
Acid Mine Drainage (AMD) and hydrometallurgical wastewater are products of extractive activities that pose environmental risks as they contain heavy metals. The contents of these streams, which is dominated by iron, necessitates an effective treatment protocol. The tendency of iron to precipitate as a sludge has drawn attention to the mechanisms and the associated kinetics of Fe(III) oxyhydroxide precipitation and the post precipitation solidliquid separation processes within the high density sludge (HDS) treatment process. The HDS process is affordable to operate and has the potential benefit of the Fe(III) oxyhydroxide precipitates removing other pollutants through coprecipitation and adsorption, but it has its own shortcomings. These include, but are not limited to, the tendency of lime to be affected by armouring which hinders further lime dissolution, the decreased solubility of lime at high pH and elevated temperature and the formation of a gelatinous low-density sludge comprised of minuscule particles of Fe(III) oxyhydroxides and gypsum. The sludge is characterized by poor dewatering behaviour and postneutralization instability which increases the risk of the adsorbed or encapsulated dissolved metals to re-leach from the disposal sites, thus lessening the likelihood for metal value recovery, waste material reuse or recycle. These negative attributes result in considerable water losses and a large land area being required for sludge disposal to landfill. The literature reviewed indicates that researchers have not reached a consensus on the actual causes of sludge formation and transformation in the course of Fe(III) oxyhydroxide precipitation, with reported reaction kinetics and mechanisms being significantly different. In light of the above difficulties and lack of sufficient progress in body of knowledge, the objectives of the current research were - to gain an in-depth understanding of the dewatering behaviour of primary Fe(III) oxyhydroxide precipitates through investigating the effect of Fe(III) concentration; [Fe(III)] and OH/Fe molar ratios on the performance (settling and filtration rates and specific resistance to filtration - SRF) of products generated in the precipitation process so as to establish the mechanistic relationships that exist, and - to understand the mechanisms and kinetics through which ageing of secondary Fe(III) oxyhydroxide precipitates occurs at elevated temperature and prolonged ageing time and to infer the effects of ageing on the dewatering behaviour of secondary Fe(III) oxyhydroxide precipitates. The mineral phase identification, though acknowledged to be valuable in iron precipitation, was seen to have negligible value in relation to describing dewatering behaviour, hence was not focused on. In order to achieve the objectives above, experiments were conducted in a 1.5 L glass mixed-suspension-mixed-product-removal (MSMPR) reactor under ambient laboratory temperature at 21 ± 1 °C. The agitated MSMPR was equipped with a lid containing ports for pH and temperature probes and four uniformly spaced stainless steel baffles to maximize mixing of the reagents. A synthetic acid mine drainage (SAMD) solution made from aqueous Fe2(SO4)3 was treated in the MSMPR reactor with a reagent grade Ca(OH)2 aqueous stream, with the Ca(OH)2 solution being used for pH adjustment thereby effecting neutralization and precipitation. A residence time of 15 minutes, as estimated from the reactor volume and feed solution flow rate, was used. The number of residence times for steady state attainment were identified as 16 from the particle size distribution (PSD) measurements, although the reactor was allowed to run up to 19 residence times (19 τ = 575 min) before sampling commenced. The ferric concentration ([Fe(III)]) in the feed was kept constant at six different levels of 50, 100, 200, 300, 400 and 800 mg L-1 (± 5 mg L-1 ) whilst adding the corresponding OH, at a molar ratio (OH/Fe - referred to as R) of 3, from the Ca(OH)2 solution. The reaction conditions were such that no gypsum was precipitated. The experiments to investigate the effect of molar ratios were conducted at OH/Fe molar ratios ranging from 3/1 (R = 3), 2.5/1 (R = 2.5) and 2/1 (R = 2) whilst the [Fe(III)] in the feed was kept constant at 100, 300, and 800 mg L-1 (± 5 mg L-1 ). The experiments to aid the understanding of ageing effects on the product characteristics (particle size, PSD, morphology and structure) and dewatering behaviour were conducted under two regimes, the continuous and the batch system. Under continuous conditions and a residence time of 15 minutes, the feed [Fe(III)] into the primary reactor (MSMPR) was set at 100, 300, and 800 mg L-1 and the aqueous stream of reagent grade Ca(OH)2 was added at a molar ratio of OH/Fe of 2.5. The primary reactor was set up on a secure elevated platform and was operated such that the overflow was continuously fed into a 1 L jacketed glass MSMPR reactor (ageing reactor). The ageing reactor was supplied with heated deionized water, operated at 30, 40 and 50 (± 1) °C and agitated at a rate of 230 rpm by a four bladed 45° pitched blade turbine. The batch ageing experiments were conducted in a 1 L jacketed reactor which was allowed to attain the setpoint temperature of 40 ± 1 °C before being filled with fresh Fe(III) oxyhydroxides from the primary reactor precipitated at a molar ratio of OH/Fe of 2.5 (R = 2.5) and [Fe(III)] of 300 mg L-1 . The agitated (230 rpm) reactor was run for 24 hours with samples collected at set times of 1, 2, 4, 6, 7, 8, 9, 10, 16 and 24 hours. The PSD results of the samples were used to establish the mechanisms and kinetics of the system by using the method of moments. The samples taken from the conditions investigated, as outlined above, were analysed for [Fe(III)] in the feed, precipitate and supernatant using spectrophotometry and the 1–10 phenanthroline method as the basis. Spectrophotometry was also used to determine the calcium and sulphate concentrations in the feed, precipitate and supernatant. The PSD and aqueous specific surface area were measured by means of laser diffraction that used static light scattering. Surface charge inferences were made through zeta potential measurements (ζ-potential) using electrophoresis to determine the isoelectric point (IEP). The pH dependence of the ζ-potential was investigated using multi-purpose titrations (MPT-2) with the titrants being 0.01 M H2SO4 and 0.01 M and NaOH. The crystal habit was analysed using scanning electron microscopy (SEM) whilst a combination of SEM with EDX was used for composition determination. Transmission electron microscopy was used to determine the morphology and size. The slurry viscosity was measured using a rheometer operating with the vane and cup arrangement. Iron mineral phase identification was done through Raman microscopy and XRD in order to verify if the mineral phases from a slurry based analysis and a solid sample analysis were the same. The initial studies on the dewatering behaviour indicated that the [Fe(III)] in the feed influenced (to varying extents) the dewatering trend of the precipitation product, via particle size, particle size distribution (PSD), surface charge, morphology and structure. It was established that there was a corresponding change in product characteristics and performance as the [Fe(III)] was increased. A transition was observed at [Fe(III)] of 300 mg L-1 where the settling rate (2.4 ± 0.04 mm min-1 ), particle size (D4,3 of 27 µm) and supersaturation passed through a maximum whilst the filtration rate (3 ± 0.46 cm3 /cm2 /min) and zeta potential approached a minimum. These conditions resulted in enhanced agglomeration, with the improved dewatering behaviour being attributed to a dense network of interlocked and interconnected bridges in the crystal habit of the particles. The results did show that there was a complicated relationship between the underlying micro- and nano-scale properties and the product performance from which dewatering behaviour is inferred. The OH/Fe molar ratio variations were described as low (R = 2.5) and high (R = 3) due to contact nucleation prompting the exclusion of the R = 2 results from further analysis. These molar ratios had an effect on product performance which was improved at the low OH/ Fe molar ratio. A low R positively affected the product characteristics which led to the fastest settling rate of 3.3 ± 0.2 mm min-1 , an increase in the filtration rate from 3.7 ± 0.4 to 5.1 ± 0.5 cm3 cm-2 min-1 and a decrease in the specific resistance to filtration (SRF) from 1.42 x 1012 to 6.71 x 1011 m kg-1 at R = 2.5 and a [Fe(III)] = 300 mg L-1 . The improved product performance was attributed to the dominance of large (D4,3 of 48.3± 0.05 µm and D3,2 of 30.8 ± 0.05 µm), regularly shaped particles which had a unimodal distribution and a notable decrease in the peak number of fine particles from 3.5 × 1013 (1 µm size) to 1.7 × 1012 (3.90 µm size). The Fe(III) oxyhydroxides formed at [Fe(III)] of 100 and 800 mg L-1 displayed insignificant product performance changes with variation in R with the exception of the 800 mg L-1 case which produced the largest change in settling rate (threefold – from 0.8 to 2.4 ± 0.2 mm min-1 ) at R = 2.5. These results reinforced the change in settling and dewatering behaviour observed at [Fe(III)] of 300 mg L-1 . It was noted that the lower R value (R = 2.5) resulted in a lower pH in solution, leading to decreased nucleation. However, higher agglomeration rates were observed, contrary to other studies. This was attributed, in the present study at low R, to a reduction in the surface charge related electrostatic repulsion, whilst van der Waals attractive forces had been favoured by the decrease in supersaturation. The product performance of the precipitates which underwent structural maturation in a continuous system were found to improve after elevated temperature treatment. The highest settling rate was found to have been reached at 40 °C and at [Fe(III)] of 300 mg L1 . This was ascribed to the increase in agglomeration which yielded a high D4,3 (26.3 ± 0.05 µm) mean particle size at this temperature; hence bigger particles implied faster settling. The filterability of the aged precipitates, at a given [Fe(III)], passed through a maximum as the temperature increased. Another transition was observed at Fe(III) of 300 mg L-1 where there was a decrease in surface charge with an increase in temperature as evidenced by the low zeta potential values and a steady state pH which was close to the isoelectric point. This was evidence of a circum-neutral surface charge that favoured agglomeration. The change in micro and nano-structure was seen in the image analysis results. However, these imaging results show evidence of deagglomeration at 50 °C which probably explains the improved dewatering behaviour. The batch ageing system revealed that structural maturation in the ageing process, at elevated temperature, has multiple particle rate processes that occur simultaneously but that which one dominates varies with time. The ageing process results identified four broad time intervals, namely 0 to 6, 6 to 8, 8 to 10 and 10 to 24 hours, through which the different mechanisms were active. The settling trend for the samples collected at the different ageing times displayed a high initial settling rate within the free settling zone of the settling curve. The solids from interval 1 and 2 (0 to 6 and 6 to 8 h) displayed the fastest settling rates within the hindered settling zone with interval 2 solids dominating the compression settling zone. It was noted, however that no significant improvements in settleability were observed with an increase in ageing time except at 8 hours. The filterability on the other hand experienced improvements with ageing especially in the interval 3 and 4 (8 to 10 and 10 to 24 h) where the specific resistance to filtration (SRF) was at its lowest value of 8.78 × 1011 m kg-1 at 8 hours. This was attributed to a combination of an increase in particle size, a decrease in the number of fine particles and a transition in the crystal habit and morphology of the particles as evidenced in the image analysis findings. The product performance followed a trend where it decreased at the onset of interval 1 and remained fairly constant throughout the interval. The onset of interval 2 saw an increase in product performance which reached a distinct maximum at 8 hours after which it reverted back, interval 3 and 4, to levels similar to those in interval 2. The mechanisms that were inferred from the moments of the distribution alluded to the nucleation of new particles (interval 1), the agglomeration and limited growth of those particles which involved structural incorporation (at 8 hours in interval 2) and transformation (of ferrihydrite into goethite particles via a dissolution and reprecipitation process which led to the goethite being sparsely distributed on top of the ferrihydrite base) (interval 3 and 4). The graphical illustration of these processes and their impact on settling and dewatering behaviour is illustrated below. The findings of this work on primary precipitation and ageing of iron during lime neutralization have implications on how iron is treated in AMD and hydrometallurgical processes. A slight elevation in post-precipitation operating temperature under reduced lime usage offers an attractive alternative to improving dewatering behaviour of the precipitated sludge with the potential of reducing metal leachate from landfills.